Enhanced Electrochemical Performance of Ultracentrifugation-Derived nc-Li3VO4/MWCNT Composites for Hybrid Supercapacitors - Iwama, Etsuro; Kawabata, Nozomi; Nishio, Nagare; Kisu, Kazuaki; Miyamoto, Junichi; Naoi, Wako; Rozier, Patrick; Simon, Patrice; Naoi, Katsuhiko (ACS nano, 2016)
Nanocrystalline Li3VO4 dispersed within multiwalled carbon nanotubes (MWCNTs) was prepared using an ultracentrifugation (uc) process and electrochemically characterized in Li-containing electrolyte. When charged and discharged down to 0.1 V vs Li, the material reached 330 mAh g–1 (per composite) at an average voltage of about 1.0 V vs Li, with more than 50% capacity retention at a high current density of 20 A g–1. This current corresponds to a nearly 500C rate (7.2 s) for a porous carbon electrode normally used in electric double-layer capacitor devices (1C = 40 mA g–1 per activated carbon). The irreversible structure transformation during the first lithiation, assimilated as an activation process, was elucidated by careful investigation of in operando X-ray diffraction and X-ray absorption fine structure measurements. The activation process switches the reaction mechanism from a slow “two-phase” to a fast “solid-solution” in a limited voltage range (2.5–0.76 V vs Li), still keeping the capacity as high as 115 mAh g–1 (per composite). The uc-Li3VO4 composite operated in this potential range after the activation process allows fast Li+ intercalation/deintercalation with a small voltage hysteresis, leading to higher energy efficiency. It offers a promising alternative to replace high-rate Li4Ti5O12 electrodes in hybrid supercapacitor applications.